Imitation Bait Colour of Skipjack Pole and Line - Gondo Puspito (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2010)
A serial experimental fishing using skipjack pole and line had been carried out for 14 days from July to October 2007 in Banda Sea. The aim was to obtain the most productive colour of imitation bait to catch skipjack. The research tested three colours of imitation bait those were red, silver and green. Result showed that the silver colour of imitation bait caught more skipjack than those two other colours. Its hook rate was 0.67 fish/minute, followed by red and green with hook rate of 0,58 fish/minute and 0.47 fish/minute. Key Words: Imitation Bait, Life Bait, Pole and Line, Skipjack.